Knowledge, attitude, and practice in communication assessment of speech-language pathologists working with adolescents with mental health concerns. - Wallis, Adele K.; Westerveld, Marleen F.; McKenzie, Matthew L. (International Journal of Speech-Language Pathology, 2026)
Purpose: The recovery model underlying mental health services emphasises the importance of the voice of the adolescent client in identifying needs, goals, and negotiating intervention. This study aimed to characterise speech-language pathologists' (SLPs) knowledge, attitude, and practice in relation to communication assessment of adolescents, focusing on adolescents with mental health concerns and the use of discourse sampling and analysis. Method: An online survey using a Knowledge, Attitude, Practice framework gathered data from 43 English-speaking SLPs. SLPs responded, using a five-point Likert scale, to closed statements regarding perceived knowledge, attitude, and practice in approaches to communication assessment. Survey items relating to discourse sampling and analysis were aggregated into subscales and six statements related to assessment of adolescents with mental health concerns. A final, open-ended question invited comments on changing clinical practice. Result: A strong positive correlation was found between knowledge and practice; with a weak, positive correlation between knowledge and attitude. Conclusion: SLPs are aware of the benefits of a comprehensive communication assessment. However, greater knowledge and experience is needed to incorporate more formalised approaches into clinical practice, especially as it relates to social and emotional outcomes. Participants' comments suggest that professional learning communities may be helpful in delivering this outcome.